PENDIDIKAN AKHLAK DI INDONESIA: STUDI PEMIKIRAN IBNU SINA - Zidan Abid Maulana; Fadila Elma Ramadhani (CV. Amerta Media, 2022)
Ibn Sina as one of the figures whose thoughts are quite influential in the field of education. He concerned about the moral aspect in education. The focus of attention from his educational philosophy is educating children by cultivating the right religious abilities, because religious education is the basis for achieving the goals of moral education. He has many thoughts about ideal educational concepts that are closely related and related to moral education in Indonesia, such us in schools or educational institutions, this issue applies in general and involves various parties related to the moral education process in Indonesia. School or institution environment. In this study, the authors will examine more deeply about how moral education exists in Indonesia and Ibn Sina's thoughts on moral education. The method used by the authors is descriptive qualitative analysis and the type of research used is library research. The results of this study are the concepts and thoughts of Ibn Sina regarding moral education can be applied to education in Indonesia, this is because there is nothing contrary to Ibn Sina's thoughts with the conditions that exist in Indonesia, even his thoughts can also overcome various problems. In Indonesia related to moral education. Keywords: Moral, Education, Ibn Sina